2002
DOI: 10.1038/nm746
|View full text |Cite
|
Sign up to set email alerts
|

Blockage of Ca2+-permeable AMPA receptors suppresses migration and induces apoptosis in human glioblastoma cells

Abstract: Glioblastoma multiforme is the most undifferentiated type of brain tumor, and its prognosis is extremely poor. Glioblastoma cells exhibit highly migratory and invasive behavior, which makes surgical intervention unsuccessful. Here, we showed that glioblastoma cells express Ca(2+)-permeable alpha-amino-3-hydroxy-5-methyl-4-isoxazolepropionate (AMPA)-type glutamate receptors assembled from the GluR1 and/or GluR4 subunits, and that their conversion to Ca(2+)-impermeable receptors by adenovirus-mediated transfer o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
295
1
6

Year Published

2004
2004
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 283 publications
(313 citation statements)
references
References 31 publications
11
295
1
6
Order By: Relevance
“…Moreover, adenoviral-mediated delivery of edited and thus Ca 2 þ impermeable GluR2 into CGNH-89 glioma cells impaired their proliferative activity and increased apoptosis. Conversely, overexpression of the unedited, Ca 2 þ permeable GluR2(Q) subunit augmented CGNH-89 glioma cell proliferation (Ishiuchi et al, 2002). In clear contrast to these studies, it has been recently suggested that glioma cells survive glutamate-rich, excitotoxic environment due to intrinsic glutamate receptor inactivation, which is supported by the finding that GluR subunits are transcriptionally downregulated in glioma specimens (van Vuurden et al, 2009). Owing to this caveat and the apparent importance of glutamate signaling for potential glioma therapy, we analyzed in detail the effects of genetic and pharmaco logical interference with glutamate secretion and cystine incorporation mediated by system X c À as well as glutamate receptor agonism and antagonism on glioma growth in vitro and ex vivo.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Moreover, adenoviral-mediated delivery of edited and thus Ca 2 þ impermeable GluR2 into CGNH-89 glioma cells impaired their proliferative activity and increased apoptosis. Conversely, overexpression of the unedited, Ca 2 þ permeable GluR2(Q) subunit augmented CGNH-89 glioma cell proliferation (Ishiuchi et al, 2002). In clear contrast to these studies, it has been recently suggested that glioma cells survive glutamate-rich, excitotoxic environment due to intrinsic glutamate receptor inactivation, which is supported by the finding that GluR subunits are transcriptionally downregulated in glioma specimens (van Vuurden et al, 2009). Owing to this caveat and the apparent importance of glutamate signaling for potential glioma therapy, we analyzed in detail the effects of genetic and pharmaco logical interference with glutamate secretion and cystine incorporation mediated by system X c À as well as glutamate receptor agonism and antagonism on glioma growth in vitro and ex vivo.…”
Section: Introductionmentioning
confidence: 98%
“…Even though the glioma-promoting properties of glutamate release by glioma cells appear to be without doubt, the underlying mechanisms are still poorly understood. Besides neurotoxic effects, some studies assume that extracellular glutamate promotes glioma proliferation in an autocrine or paracrine manner by activation of ionotropic glutamate receptors on gliomas, especially of the (RS)-a-Amino-3-hydroxy-5-methylisoxazole-4-propionic acid hydrate (AMPA) subtype (Ishiuchi et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…In migratory glioma cells, similar Ca 2+ oscillations are reported in response to activation of ACh-R (Bordey et al, 2000), which activate charybdotoxin-sensitive BK K + channels. Moreover, glioma cells express Ca 2+ -permeable AMPA receptors, and Ca 2+ influx through these receptors is required for cell migration (Ishiuchi et al, 2002). Hence, receptormediated activation of Ca 2+ influx into either migratory granule cells or glioma cells appears to be a prerequisite for cell migration: we suspect that this Ca 2+ signal is instructive with regards to cell-volume changes that occur down-stream.…”
Section: Discussionmentioning
confidence: 96%
“…Accordingly, the therapeutic strategies that have been proposed to counteract the Glu-supporting effects on glioma invasiveness which are based on the use of Glu release inhibitors and Glu receptor antagonists [11, 13, 14] are precisely the same as those proposed for the treatment of acute neurodegenerative disorders involving excess Glu in brain such as stroke or head trauma.…”
Section: Introductionmentioning
confidence: 99%